Анализа корелације нивоа цитокина у серуму и имунолошких фактора упале код циротичне портне хипертензије: Нивои цитокина у серуму и имуни инфламаторни фактори код циротичне порталне хипертензије - Yu, Yafeng; Lan, Zhiqiong; Huang, Zhi-Ren; Hu, Lingqin (Journal of Medical Biochemistry, 2025)
Objective: To investigate alterations in immune inflammatory factors and variables including procalcitonin (PCT), prostaglandin E (PGE), and serum C-reactive protein (CRP) in individuals with cirrhotic portal hypertension.Methods: From March 2020 to March 2025, 81 patients with cirrhotic portal hypertension and 50 healthy volunteers were hospitalized to our hospital. These people were divided into two groups: the portal hypertension group and the control group. Aspartate aminotransferase (AST), albumin (ALB), total bilirubin (TBIL), alanine aminotransferase (ALT), and portal vein inner diameter (Pvd) were measured. Serum cytokines such CRP, PCT, and PGE were measured, as well as CD4+/CD8+ T cell and CD3+, CD4+, and CD8+ T lymphocyte percentages.Results: The group with portal hypertension had considerably lower ALB than the control group (P
Keywords: Цироза јетре; Портална хипертензија; Имунски инфламаторни фактори; Нивои цитокина